Chair for the session ”Market Microstructure IV”, European Financial Management Association (EFMA) Conference - Tsouknidis, Dimitris (My University, 2026)
Chair for the session ”Market Microstructure IV”, European Financial Management Association (EFMA) Conference, Athens, Greece, 28 June - 1 July 2017.